2018
DOI: 10.1089/ars.2017.7112
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence, Neurological Function, and Redox State

Abstract: It is still unknown which alterations in the overall metabolism can stimulate senescence induction in the aged brain, what are the mechanisms and signaling pathways, and what is their relationship to NDD development. The understanding of these processes will expose new targets to intervene age-associated pathologies.-Antioxid. Redox Signal. 28, 1704-1723.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 182 publications
2
25
0
Order By: Relevance
“…The main functions of the endogenous antioxidant enzyme system are to maintain the steady state of ROS in the internal environment and remove excess ROS [ 31 ]. Therefore, numerous researches have shown that treatment with antioxidants could delay the cellular senescence [ 32 ]. Zeng et al [ 33 ] reported that Se-enriched rice could enhance the activity of antioxidant enzymes and prevent the formation of oxidative products.…”
Section: Discussionmentioning
confidence: 99%
“…The main functions of the endogenous antioxidant enzyme system are to maintain the steady state of ROS in the internal environment and remove excess ROS [ 31 ]. Therefore, numerous researches have shown that treatment with antioxidants could delay the cellular senescence [ 32 ]. Zeng et al [ 33 ] reported that Se-enriched rice could enhance the activity of antioxidant enzymes and prevent the formation of oxidative products.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is one of the major factors to contribute to cellular senescence, and a typical feature of senescence is a shift to a prooxidant redox state. Therefore, numerous researches have shown that treatment with antioxidants could delay the cellular senescence [38]. Moreover, SOD, CAT, and VE are the important members of this antioxidant system [10].…”
Section: Discussionmentioning
confidence: 99%
“…Senescent cells are detectable in the mammalian brain, specifically in replication competent glial cells, where they could contribute to neurodegeneration by secreting pro‐inflammatory SASP factors and/or deregulating cellular crosstalk useful for the structural and functional neuron‐glial interaction that maintains neuronal homeostasis . Senescence markers have been observed in all the different cell populations of the brain, including neurons and components of innate immunity, and they correlate with normal or pathological aging conditions . Indeed, immune responses in the CNS are common, despite its perception as a site of immune privilege .…”
Section: Introductionmentioning
confidence: 99%